Perancangan Sistem Informasi Penggajian Karyawan Berbasis Web Dengan Metode Waterfall (Studi Kasus: PT. Sakura Java Indonesia) - Wiyanto; Irfan Hariyadi (DPPM Universitas Pelita Bangsa, 2025)
Payroll is a form of remuneration given to employees for their contributions to achieving company goals. At PT. Sakura Java Indonesia, the payroll data processing system is still handled manually. Employee data is recorded in a special book each month, and salary reports are provided using conventional methods. This manual process often leads to data inaccuracies and inconsistencies. In addition, verifying payroll data requires significant time and effort, and data security remains inadequate due to the lack of a computerized system. To address these issues, a web-based payroll information system was designed using the Waterfall development method. The system was developed with PHP as the programming language and MySQL as the database. This proposed system aims to improve accuracy, efficiency, and data security in payroll processing. By digitizing and integrating payroll activities, the company can streamline data input, calculation, and reporting processes. As a result, payroll management becomes more effective, efficient, and reliable in supporting organizational operations.